Pengaruh Kompensasi dan Kepuasan Kerja terhadap Produktivitas Kerja karyawan PT. Bangun Makmur Medan - Farina Jessen Yap; Ronauli Fransiska Pasaribu (Pusat Riset dan Inovasi Nasional, 2022)
This research was conducted at PT. Bangun Makmur Medan. Work productivity that has not reached the company's target because there are still shortcomings that occur to employees when viewed with data in the last 5 years, not all employees can achieve work productivity targets that have not reached the company's target because there are still shortages that occur when viewed with data in 5 years Finally, not all employees can reach the target. Compensation is still very low due to the bonuses made by companies that have not been maximal for employees who have worked optimally. Employees are not satisfied with what they receive from their co-workers who cannot work together and the lack of opportunities for employees to get promotion opportunities and the amount of bonuses received is not yet in line with expectations because the bonuses made by the company are not maximized with employees who have worked optimally. The population is 129 employees and the sample in this study was 98 employees. The sampling technique used is sample random sampling. The technique of collecting data is by pembainigain kueisoner, interviews and documentation studies. Data analysis uses validity and reliability test, classic assumption test, multiple linear regression analysis, determinant coefficient and hypothesis testing.Conclusions in the study that simultaneous Compensation and Job Satisfaction influence the Work Productivity of PT. Bangun Makmur Medan. Partially Compensation and Job Satisfaction influence the Work Productivity of PT. Bangun Makmur Medan. Partially Job Satisfaction influences the Work Productivity of PT. Bangun Makmur Medan. The magnitude of the coefficient of determination that value .10 means compensation and job satisfaction can explain employee work productivity by 31% and the remaining 69% (100-31) is influenced by other variables outside of this study such as: work motivation, career development, work environment and so on